Reversing LeTID in PV power plants: a feasibility study - Fokuhl Esther; Gebhardt Paul; Schnabel Erdmut; Kleinhans Alexander; Armbruster Cornelius; Mikolajick Thomas; Wesselak Viktor; Philipp Daniel (EPJ Photovoltaics)
Light and elevated Temperature Induced Degradation (LeTID) is likely causing strong yield losses in a significant number of photovoltaic (PV) power plants which were commissioned in the late 2010s. In this work, a procedure for an in-field recovery using overnight current injection to trigger temporary recovery of LeTID is presented. The general feasibility of such a procedure is first demonstrated by climatic chamber experiments on strongly degraded mc-Si PERC PV modules. Within the screened test conditions, a temporary recovery procedure with high currents and low module temperatures is most promising for an economic application in PV power plants. An outdoor experiment with current injection during nights and MPP tracking during days confirmed the possibility to recover LeTID in PV power plants. By injecting a pulsed current, the heating of the modules caused by the current injection was strongly reduced compared to the heating at constant current injection. Recommendations for the application of a procedure in PV power plants are given based on the required energy expenditure and cost.